2008
DOI: 10.1148/radiol.2471070688
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage T2 Assessment at 3-T MR Imaging: In Vivo Differentiation of Normal Hyaline Cartilage from Reparative Tissue after Two Cartilage Repair Procedures—Initial Experience

Abstract: Quantitative T2 mapping seems to reflect differences in repair tissues formed after two surgical cartilage repair procedures. (c) RSNA, 2008.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
183
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(204 citation statements)
references
References 40 publications
16
183
1
4
Order By: Relevance
“…99 Histological and MRI-based follow-up studies have shown that zonal organization of the de novo tissues can range from disorganized (Fig. 4D 100 ) to zonally developed in terms of T2 relaxation times, 101 which are related to the collagen network. 102 Assessment of zonal markers has not been determined for these tissues.…”
Section: Scaffold-based Approachesmentioning
confidence: 99%
“…99 Histological and MRI-based follow-up studies have shown that zonal organization of the de novo tissues can range from disorganized (Fig. 4D 100 ) to zonally developed in terms of T2 relaxation times, 101 which are related to the collagen network. 102 Assessment of zonal markers has not been determined for these tissues.…”
Section: Scaffold-based Approachesmentioning
confidence: 99%
“…Ayrıca fiziksel aktivite- [58]. T2 haritalama tekniğinin kıkırdak onarı-mının zamanla takip edilmesinde kullanılabilir olduğu gösterilmiş olup çoğu klinik MR sisteminde kolayca uygulanabilir hal almıştır [59].…”
Section: T2 Haritalama Tekniğiunclassified
“…Günümüzde klinik olarak 1.5 T daha yaygın olmak üzere bazı merkezlerde 3.0 T MR sistemleri mevcuttur. 3.0 T sistemleri diz kıkırdağının morfolojisi ve bileşenine yönelik görüntüleme metodlarını optimize etmek için umut verici sonuçlar göstermiştir [35,51,59]. Aynı veri elde etme süresinde 3.0 T da 1.5 T'ye göre sinyal-gürültü oranı kabaca iki kat fazla olduğundan görüntü kalitesi ve uzaysal çözü-nürlüğü çok iyidir.…”
Section: Manyetik Alan Gücünün Kıkırdak Mr Görüntülemeye Etkisiunclassified
“…Higher T2 is seen in early stages of degenerative osteoarthritis (Dunn, Lu et al 2004). Although T2 maps do not demonstrate any relationship between T2 and grade of defect or arthritic change (marker of severity of disease) (Koff, Amrami et al 2007), they have demonstrated the ability to longitudinally assess cartilage repair or restoration tissue following surgery (Welsch, Mamisch et al 2008). Just as dGEMRIC may measure proteoglycan content, T1-rho values can also be used to assess extracellular matrix composition.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%